United Nations Juridical Yearbook 2012 - United Nations (United Nations, 2013)
Mandated by General Assembly resolution 1814 (XVII) of 18 December 1962, this book has been published on an annual basis since 1963. It contains documentary materials of a legal character concerning the United Nations and related intergovernmental organizations. The present volume, which is the forty-ninth of the series, covers activities undertaken in 2012 and contains information such as legislative texts and treaties, a general review of the legal activities of the United Nations and related intergovernmental organizations, a list of judgments, advisory opinions and selected decisions rendered by international tribunals, as well as a selected bibliography listing works and articles of a legal character relating to the work of the United Nations and related intergovernmental organizations.